2019
DOI: 10.1029/2018jg004723
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Ecosystem Engineer, the Leaf‐Cutter Ant Atta cephalotes, on Soil CO2 Dynamics in a Wet Tropical Rainforest

Abstract: Leaf-cutter ants are dominant herbivores that disturb the soil and create biogeochemical hot spots. We studied how leaf-cutter ant Atta cephalotes impacts soil CO 2 dynamics in a wet Neotropical forest. We measured soil CO 2 concentration monthly over 2.5 years at multiple depths in nonnest and nest soils (some of which were abandoned during the study) and assessed CO 2 production. We also measured nest and nonnest soil efflux, nest vent efflux, and vent concentration. Nest soils exhibited lower CO 2 accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 85 publications
(80 reference statements)
0
43
0
Order By: Relevance
“…A recent study found soil CO 2 concentration significantly lower in A. cephalotes nest soils compared with non‐nest soils during wet periods, but this difference was not significant during dry periods. For the same precipitation amounts, nest soils accumulated less CO 2 than non‐nest soils (Fernandez‐Bou et al, ). These findings are attributed to the internal network of tunnels and chambers that act as a preferential flow path for the surrounding CO 2 produced in the soil matrix to find its way out to the atmosphere.…”
Section: Knowledge Gap 4—nest Outputsmentioning
confidence: 95%
See 4 more Smart Citations
“…A recent study found soil CO 2 concentration significantly lower in A. cephalotes nest soils compared with non‐nest soils during wet periods, but this difference was not significant during dry periods. For the same precipitation amounts, nest soils accumulated less CO 2 than non‐nest soils (Fernandez‐Bou et al, ). These findings are attributed to the internal network of tunnels and chambers that act as a preferential flow path for the surrounding CO 2 produced in the soil matrix to find its way out to the atmosphere.…”
Section: Knowledge Gap 4—nest Outputsmentioning
confidence: 95%
“…Normally produced by temperature differences, free convection is a less efficient mechanism for nest ventilation than forced convection. Nevertheless, it can be a significant mechanism for gas transport when cool, dense gas overlies warm, less dense gas (Fernandez‐Bou et al, ). Elevated relative humidity also decreases air density (at constant pressure) since water molecules have lower molecular weights than dry air molecules (moist air rises over dry air).…”
Section: Knowledge Gap 4—nest Outputsmentioning
confidence: 99%
See 3 more Smart Citations